Regioselectively α- and β-alkynylated BODIPY dyes via gold(I)-catalyzed direct C–H functionalization and their photophysical properties - Shimada, Takahide; Mori, Shigeki; Ishida, Masatoshi; Furuta, Hiroyuki (Beilstein Journal of Organic Chemistry, 2020)
A series of α- and β-ethynyl-substituted BODIPY derivatives (3a, 4a, 5a, 5b, 6a, 6b) were synthesized by gold(I)-catalyzed direct C–H alkynylation reactions of dipyrromethane and BODIPY, respectively, with ethynylbenziodoxolone (EBX) in a regioselective manner. Depending on the position of the ethynyl substituent in the BODIPY skeleton, the photophysical properties of the resulting α- and β-substituted BODIPYs are notably altered. The lowest S0–S1 transition absorbance and fluorescence bands are both bathochromically shifted as the number of substituents increases, while the emission quantum yields of the β-ethynylated derivatives are significantly lower than those of α-ethynylated ones. The current method should be useful for fine-tuning of the photophysical properties of BODIPY dyes as well as for constructing BODIPY-based building cores for functional π-materials.
Keywords: alkynylation; BODIPY; direct C–H functionalization; gold(I)